(untitled) (Bangladesh Journal of Bioethics, 2016)
Non-communicable diseases (NCDs) disproportionately affect low and middle-income countries where nearly three quarters of NCD deaths occur. Bangladesh is also in NCD burden. This cross-sectional study was done on 50 health facilities centres at Gazipur district in Bangladesh from July 2015 to December 2015 to introduce SARA for better monitoring and evaluation of non-communicable diseases health service delivery. The General Service readiness index score was 61.52% refers to the fact that about 62% of all the facilities were ready to provide general services like basic amenities, basic equipment, standard precautions for infection prevention, and diagnostic capacity and essential medicines to the patients. But in case of non-communicable diseases, among all the health facilities 40% had chronic respiratory disease and cardiovascular diseases diagnosis/ management and only 32% had availability of diabetes diagnosis/management. Overall readiness score was 52% in chronic respiratory disease, 73% in cardiovascular disease and 70% in diabetes. Therefore, service availability and readiness of the health facilities to provide NCD related health services were not up to the mark for facing future targets. A full-scale census survey of all the facilities of the study area would give a better understanding of the availability and service readiness.